The perception of personal space and crowding during COVID-19: An example of grocery shopping - Betul Sahin (2022)
Covid-19 has reshaped the daily lives of people all around the world. Many regulations and changes have been made by the authorities in order to reduce the risk of transmission of the virus. Significantly, the regulations made by the government aim to reduce the number of people per square meter in closed areas and to increase the social distance between people. These regulations bring along new personal space and crowding perceptions. In this context, people's behaviors in many public spaces, from public transportation to grocery shopping, have gained a new texture. This change not only changed the perspective of the place but also caused a change in the perspective of people for one another. In this paper, environmental regulations aiming to adapt people's behaviors to social distance due to Covid-19 are examined in terms of personal space and crowding concepts. The purpose is to conduct an online interview with a retrospective approach and present the data as a narrative to determine the participants' perceptions of the random sampling method about personal space and crowding concepts before and after the pandemic. The research data were analyzed using the content analysis method in the QRS Nvivo qualitative data analysis program. In the results of the study, it was revealed that people's need for personal space in closed areas increased, and the crowding perception differed from the pre-pandemic due to psychological reasons through the example of grocery shopping. Covid-19 salgını, dünyanın her yerinde insanların günlük yaşamlarını yeniden şekillendirmiştir. Yetkililer tarafından virüsün bulaşma riskini azaltmak için birçok düzenleme ve değişiklik yapılmıştır. Dünya Sağlık örgütü tarafından yapılan uyarılar ve merkezi otoritelerce yapılan düzenlemeler kapalı alanlarda metrekareye düşen kişi sayısını azaltmayı ve insanlar arasındaki sosyal mesafeyi artırmayı hedeflemektedir. Bu düzenlemeler yeni kişisel alan ve kalabalık algılarını beraberinde getirmektedir. Bu bağlamda toplu taşımadan market alışverişine kadar birçok kamusal alanda insanların davranışları yeni bir doku kazanmıştır. Bu değişim bireylerin sadece mekana bakış açılarını değiştirmekle kalmamış, aynı mekanda bulunduğu diğer insanlara bakış açılarının da değişmesine neden olmuştur. Bu araştırmada, Covid-19 nedeniyle insanların davranışlarını sosyal mesafeye uyarlamayı amaçlayan çevre düzenlemeler, kişisel alan ve kalabalık kavramları açısından incelenmektedir. Amaç, içinden geçilen değişim sürecinin bireyin kişisel alan ve kalabalık algıları üzerindeki etkisini market alışverişi örneği üzerinden ortaya koymaktır. Çalışmada katılımcıların pandemi öncesi ve sonrasında kişisel alan ve kalabalık kavramlarına ilişkin algılarını belirlemek için retrospektif bir yaklaşımla çevrimiçi görüşmeler yapılarak veri toplanmıştır. Araştırma verileri QRS Nvivo nitel veri analiz programında içerik analizi yöntemi kullanılarak analiz edilmiştir. Çalışmanın sonuçlarında market alışverişi örneği üzerinden Covid-19 salgını süresince insanların kapalı alanlarda kişisel alan ihtiyacının arttığı, kalabalık algısının psikolojik nedenlerle pandemi öncesine göre farklılaştığı ortaya koyulmuştur.